2020
DOI: 10.1007/s00431-020-03744-y
|View full text |Cite
|
Sign up to set email alerts
|

Early surfactant replacement guided by lung ultrasound in preterm newborns with RDS: the ULTRASURF randomised controlled trial

Abstract: This study aimed to investigate whether using lung ultrasound (LUS) scores in premature newborns with respiratory distress syndrome (RDS) allows for earlier surfactant therapy (within the first 3 h of life) than using FiO 2 criteria. This was a randomised, non-blinded clinical trial conducted in a neonatal intensive care unit. The inclusion criteria were newborns with a gestational age of ≤ 32 weeks and RDS. Patients meeting the inclusion criteria were randomly assigned to two groups: the ultrasound group, adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
91
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(99 citation statements)
references
References 34 publications
2
91
0
6
Order By: Relevance
“…The current treatment paradigm requires verification in properly designed clinical trials where surfactant would be LUS guided. Papers describing the use of the LUS score as a criterion for the administration of surfactant have already emerged, presenting clinical benefits of this novel approach, e.g., an increased number of ventilator-free days [ 21 ] or reduced oxygen exposure [ 36 ], while maintaining unchanged pharmaceutical expenditures [ 37 ]. It is essential that in future studies, the primary outcome is not CPAP failure, as it is at present, but the development of bronchopulmonary dysplasia.…”
Section: Discussionmentioning
confidence: 99%
“…The current treatment paradigm requires verification in properly designed clinical trials where surfactant would be LUS guided. Papers describing the use of the LUS score as a criterion for the administration of surfactant have already emerged, presenting clinical benefits of this novel approach, e.g., an increased number of ventilator-free days [ 21 ] or reduced oxygen exposure [ 36 ], while maintaining unchanged pharmaceutical expenditures [ 37 ]. It is essential that in future studies, the primary outcome is not CPAP failure, as it is at present, but the development of bronchopulmonary dysplasia.…”
Section: Discussionmentioning
confidence: 99%
“…Despite an earlier surfactant administration in the ESTER period, the authors found no differences in the need for a second dose of surfactant, days of oxygen or BPD when comparing both periods. In a recent study published by Rodriguez‐Fanjul et al 36 surfactant was administered before 3 h of life in all VPI with RDS using only LUS score to guide treatment and without finding significant differences in surfactant treatment between groups. The main concern when using only an echographic criteria to guide surfactant administration is the treatment of some patients that could have been managed with noninvasive ventilation only.…”
Section: Discussionmentioning
confidence: 99%
“…They applied the ESTHER policy and, notably, all infants in the first group reached the lung ultrasound score threshold before the momentous brink of 0.3 FiO 2 demand and received surfactant within the first hour of life (versus 6 hours in the control group). Together, these two papers provide good evidence for a timelier and more physiology-based surfactant administration in preterm babies with RDS [14,15]. Interestingly, the lung ultrasound-guided surfactant replacement reduced oxygen exposure but did not change the overall surfactant use.…”
mentioning
confidence: 76%
“…A recent quality improvement project showed that when surfactant is given based on lung ultrasound score (versus the oxygen requirement), more babies received surfactant within 3 hours of life with less oxygen exposure; this has been called ESTHER (Echography-guided Surfactant THERapy) [14]. Rodriguez Fanjul and coworkers should be commended for being the first colleagues to confirm these results in a randomized controlled trial where lung ultrasound score and FiO 2 thresholds are compared [15]. They applied the ESTHER policy and, notably, all infants in the first group reached the lung ultrasound score threshold before the momentous brink of 0.3 FiO 2 demand and received surfactant within the first hour of life (versus 6 hours in the control group).…”
mentioning
confidence: 99%